Intercostal nerve block in pediatric minimally invasive thoracic surgery - Lukošienė, Laura; Kalibatienė, Lina; Barauskas, Vidmantas (Acta medica Lituanica, 2012)
Background. Very severe postoperative pain is observed after minimal ly invasive repair of pectus excavatum (MIRPE), extremely in the early postoperative period. Pain is usually managed by either thoracic epidu ral block (TEB) or intravenous patient-controlled analgesia (PCA) with opioids. But the issue of optimal pain management is still controversial. The purpose of our study was to investigate efficiency and side effects of intercostal nerve block (ICNB) in children after MIRPE in comparison with only PCA. Materials and methods. Records of 20 patients, given PCA with mor phine (PCA group), were examined retrospectively. 27 patients, given in traoperative ICNB (single shot) and PCA with morphine (ICNB group), were examined prospectively. Postoperatively, we recorded morphine consumption, pain scores and side effects every 3 hours. Results. There was no need of the initial dose of morphine in the ICNB group. Pain scores during the first 3 hours, morphine consumption dur ing the first 3 hours and during 12 hours after surgery were significantly higher in the PCA group (p
Keywords: intercostal nerve block; children; postoperative pain